2019
DOI: 10.1002/berj.3529
|View full text |Cite
|
Sign up to set email alerts
|

‘Learning to play the game’: How schools with below average attainment can support the decision‐making processes for high‐potential learners in applying for university

Abstract: This article explores how schools with below average attainment can support high‐attaining learners in their decision‐making about university. We report on a project involving longitudinal case studies of 43 high‐achieving learners from a range of backgrounds across five institutions, during their sixth form career in 2013/14 and 2014/15, focusing on ways in which aspirations towards university develop. To understand schools’ roles in supporting learners, we draw on Hart's analytical framework which sees the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Important also in this process is recognising the institutional reactions to this situation in terms of how institutions (schools, universities and third sector organisations) understand young people from lower socioeconomic backgrounds and how they choose to support them. Rose, Tikly and Washbrook (2019) explored how schools play a critical mediating role in supporting students in their decision-making. Their research found that, particularly at 'crunch' points in students' decision-making processes, students needed ongoing support through processes of their 'choice of A-levels; selecting degree subject; receiving predicted grades; ucas applications (both content and timing in relation to grades); and receiving offers from universities' (pp.868-9).…”
Section: How Is Widening Participation In Higher Education Currently ...mentioning
confidence: 99%
“…Important also in this process is recognising the institutional reactions to this situation in terms of how institutions (schools, universities and third sector organisations) understand young people from lower socioeconomic backgrounds and how they choose to support them. Rose, Tikly and Washbrook (2019) explored how schools play a critical mediating role in supporting students in their decision-making. Their research found that, particularly at 'crunch' points in students' decision-making processes, students needed ongoing support through processes of their 'choice of A-levels; selecting degree subject; receiving predicted grades; ucas applications (both content and timing in relation to grades); and receiving offers from universities' (pp.868-9).…”
Section: How Is Widening Participation In Higher Education Currently ...mentioning
confidence: 99%
“…In schools with below‐average attainment there may be a particular need for informational support to ensure that high‐attaining students do not rule out options through lack of understanding (e.g. Rose et al., 2019). Information constraints have also been linked to the concept of undermatching, a tendency for students from less‐advantaged backgrounds to stay close to home and attend universities for which they are overqualified (Campbell et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that to solve these problems, state, businesses, and high education institution have to develop a strategy of forecasting future needs of competences based on deep analysis of the environment. To support high school students in their decision-making process, universities and schools have to collaborate and define the key elements which can ensure the deep understanding of future career options of the students (Rose et al, 2019). In other words, they must define what are the most needed and popular career options and what influence the students to choose that options.…”
Section: Introductionmentioning
confidence: 99%